Adaptation and validation of the children s anger response checklist for grade 4, 5, and 6 Lebanese students - Adhami, Nadine Nabil (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2014)
This study tackled different views about the underlying cognitive, emotional, behavioral, and physiological systems of Anger. Due to the complexity of anger, it is essential to use a multi-dimensional and comprehensive assessment tool that tackles all its underlying components and in this case it is Children s Anger Response Checklist (CARC). Not only did this study address the multi-dimensionality of anger in children, but it also tackled the limitation of not having adequate measures to assess anger s underlying cognitive processes in children.The CARC is based on Novaco s multidimensional model of anger that is built upon Bandura s Social Learning theory. Moreover, not only is there a scarcity of multidimensional anger assessment tools that target children whose ages are between 8 and 12 years old but also the Arab region lacks validated anger assessment tools for children. The procedure consisted of Item Adaptation and Validation of the CARC. Hence, 3 Educational psychologists adapted the CARC, whereby, they checked for readability, and age appropriateness then it was pilot tested (n=67). According to the pilot work, the items of the Adapted CARC measured the intensity of anger arousal and assessed the possible responses that reflected the multidimensional components of anger in children. Then the Adapted CARC was given to 404 students in grades 4, 5, and 6 from seven randomly selected private schools in Greater Beirut, Lebanon. Statistical Analysis was done that investigated the construct validity by examining convergent and divergent validity, factor structures, and reliability (test-retest reliability) of the adapted CARC. The reliability of the test both internal and over time was very good. The test proved to have a significant but low to moderate convergent and divergent validity with the M-SAI. When investigating factor analysis A-CARC subscales loaded to 3 factors that reflected the maladaptive-aggressive manifestations, maladaptive-passive manifestations and adaptive-assertive manifestations of anger. This holds with it implications for assessment and early interventions. Limitations of the study and recommendations for future studies are discussed.
: Mémoire
Keywords: Cycle primaire; Elementary Education; Psychological Tests; Tests Psychologiques